Agile Management of Teamwork of Engineering Projects - Приймак, Василь Михайлович; Корж, Б. (Київський національний університет імені Тараса Шевченка, 2019)
The problems of introduction of agile methodologies in the process of functioning of domestic enterprises in the field of engineering services are investigated. The main reasons for the transition from the traditional cascade model of project team management to agile technologies, in particular, Scrum and Kanban, are identified. The main stages of implementation of engineering service based on Scrum and Kanban methodologies according to the level of organizational maturity of the enterprise are distinguished. A combined Scrum-Kanban adaptive model has been created to enable Agile principles to be implemented in a team management system at engineering services.

Досліджено проблематику впровадження гнучких методологій у процес функціонування вітчизняних підприємств сфери інжинірингових послуг. Визначено основні причини переходу із традиційної каскадної моделі управління проектними командами на гнучкі технології, зокрема, Scrum та Kanban. Виокремлено основні етапи реалізації інжинірингової послуги на основі методологій Scrum та Kanban відповідно до рівня організаційної зрілості підприємства. Сформовано комбіновану адаптивну модель Scrum-Kanban, що надає змогу імплементувати принципи Agile в систему управління командною роботою на підприємствах сфери інжинірингових послуг.
Гнучкі моделі управління командною роботою інжинірингових проектів
Keywords: гнучкі методи управління; Agile; Scrum; Kanban; проект; проектна команда; управління проектами; Management 3.0; Project; Project Team; Project Management